Snow depth measurements in the Kaldoaivi Wilderness Area, for March 2016 - Helena Bergstedt; Annett Bartsch (PANGAEA, 2021)
Snow depth and snow water equivalent measurements were taken during March 2018 at or near most measurement points.
In: Bergstedt, H; Bartsch, A (2020): Near surface ground temperature, soil moisture and snow depth measurements in the Kaldoaivi Wilderness Area, for 2016-2018 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.912482